Factors influencing the turnover intentions in Generation Y employee: a study from Pakistan - Arif, Munazza (2020)
An increasing turnover intention in the employees from Generation Y has been detected as a critical problem for every organization regardless of its geographical location or the industry it belongs to. Generation Y is most recent cohort to join the workforce, and as it is moving deeper into the work, there is a growing evidence that suggests that Generation Y at work espouse different values and expectations from their work than the older cohorts and portray a much higher tendency of intending to leave or quit their jobs. Acknowledging the gap in the academic literature, the main purpose of this study was to “Examine the motivators that influence the intention to leave among Generation Y employees in Pakistan.”. The first theory used to develop the research framework was the Theory of Planned Behaviour. The theory contains three significant components; attitude, subjective norms and the perceived behavioural control. Frederick Herzberg’s Intrinsic and Extrinsic Motivators were used as the second base theory for this research. A closed-ended questionnaire was used to collect data from 202 Generation Y employees, which was analysed and tested using SPSS for descriptive analysis, correlation and regression. The results proposed a significant impact of Attitude, Subjective Norm and Frederick Herzberg’s Extrinsic Motivators, whereas Perceived Behavioural Control and Frederick Herzberg’s Intrinsic Motivators did not have an influential impact on the intention to leave in the Generation Y employees. The outcomes also show consistency with the theoretical facts established through literature review. The possible reasons for the outcomes in Pakistani setting and recommendations follow the analysis. These results contribute to an enriching addition to the academic literature and have opened an avenue for further research in the region.